An advertising campaign for ovaltine power - Balagtas, Louella (Animo Repository, 2000)
This group underwent training in J. Walter Thompson where they were involved in the Ovaltine Power account. After conducting an extensive Usage Attitude and Image (UAI) research on Ovaltine Power, results indicated that Ovaltine Power and Milo are almost equal in terms of awareness of the brand. In terms of usage, Milo was found to be consumed more than Ovaltine Power. Milo has higher credibility than Ovaltine Power because of its consistent image and strong presence. Milo's image is very strong, since it has been equated to sports and has been perceived as the Olympic energy drink since the 1970's. Ovaltine Power on the other hand has a weak brand image because of its inconsistencies with its positioning over the years. Ovaltine Power has very little advertising compared to Milo even through it has long been there in the market. They have low traditional and non-traditional advertising. Ovaltine Power has a very weak presence in the market because it has limited budget, which greatly affects its media spending. Due to this constraint, it has become harder for Ovaltine Power to communicate to the consumers. Milo on the other hand, has always been present in terms of advertising, which makes their brand image even stronger. The main goal of this paper, as a result of these findings shall be to reposition Ovaltine Power to another segment. It is this paper's objective to make an effective equation of Ovaltine Power to technological advancements, for it to be perceived as the drink of the new age. The present campaign shall serve as a transition from the current perception of the consumers on Ovaltine Power to the expected perception of the consumers as a result of this proposed campaign. To achieve these goals, the group decided to utilize an Integrated Marketing Communications Approach. In order to do this, the group used the Five Cs of Dean Tullao as a framework. This strategy enabled the campaign to be highly focused, yet very flexible in terms of media exposure. Aside from traditional media, this group made use of special events, advocacy public relations, and other non-traditional media. It is highly focused because all activities revolve on one theme which is also the tagline for this campaign, A Brighter Tomorrow with Ovaltine Power.